Anticancer drug discovery from Chinese medicinal herbs - Mu-Yang Huang; Le-Le Zhang; Jian Ding; Jin-Jian Lu (BMC, 2018)
Abstract Cancer is still presenting a serious threat to human health worldwide. The understanding of the complex biology of cancer and the development of oncotherapy have led to increasing treatment approaches such as targeted therapy and immunotherapy. Chinese medicinal herbs have attracted considerable attention due to their potential anticancer effects. Some natural products or formulae from Chinese medicinal herbs with directly or indirectly anticancer effects have been reported. In this article, we summarized the current progression on development of anticancer drugs from Chinese medicinal herbs, toward providing ideas for further development and application of Chinese medicinal herbs in cancer therapy.